1997
DOI: 10.1161/01.atv.17.11.2955
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Secretion of VLDL in Nondifferentiated Caco-2 Cells Stably Transfected With Human Recombinant ApoB48 cDNA

Abstract: Intestinal cells secrete apoB48-containing very low density lipoproteins (VLDLs) and chylomicrons for the transport of biliary and dietary lipids. The molecular mechanisms regulating the assembly of intestinal lipoproteins are not known due to a lack of reliable and specific cell culture models. Caco-2 (a human colon carcinoma) cells have been used to study intestinal lipid metabolism. These cells have been shown to secrete both apoB100- and apoB48-containing triglyceride (TG)-rich lipoproteins only after diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…As seen before, treatment of HepG2 cells with TGF-␤ decreased apoB secretion by ϳ25%. As expected, nondifferentiated Caco-2 cells secreted (54 Ϯ 7 ng/well) significantly smaller amounts of apoB than the differentiated cells (see above), in agreement with other studies (48,52). Nonetheless, treatment of these cells increased apoB secretion by 26% (Fig.…”
Section: Effect Of Tgf-␤ Is Independent Of the State Of Differentiatisupporting
confidence: 92%
See 1 more Smart Citation
“…As seen before, treatment of HepG2 cells with TGF-␤ decreased apoB secretion by ϳ25%. As expected, nondifferentiated Caco-2 cells secreted (54 Ϯ 7 ng/well) significantly smaller amounts of apoB than the differentiated cells (see above), in agreement with other studies (48,52). Nonetheless, treatment of these cells increased apoB secretion by 26% (Fig.…”
Section: Effect Of Tgf-␤ Is Independent Of the State Of Differentiatisupporting
confidence: 92%
“…1). The amount of apoB secreted by the control Caco-2 and HepG2 cells was 944 Ϯ 59 and 1266 Ϯ 82 ng/well, respectively, in agreement with our earlier studies (44,48,(52)(53)(54). In Caco-2 cells, TGF-␤2 showed a concentrationdependent increase in the amount of apoB secreted into the basolateral medium.…”
Section: Differential Effects Of Tgf-␤ On Apob Secretion By Caco-2 Ansupporting
confidence: 90%
“…In contrast to enterocytes which mainly synthesize apoB48, Caco-2 cells mainly synthesize apoB100 (2,(5)(6)(7)(8)(9). In a previous study, we showed that the inability of these cells to assemble CM was not due to limited synthesis of apoB48, since overexpression of apoB48 did not result in the secretion of chylomicrons (10). Furthermore, lipid absorption and transport were not impaired in mice expressing only apoB100 (11,12).…”
mentioning
confidence: 90%
“…Primary enterocytes were isolated and cultured as described (24). HepG2 and Caco-2 cell were cultured as described previously (25,26). Human apoB and apoAI secreted from cells were measured by enzyme-linked immunosorbent assay (23,27).…”
Section: Cellsmentioning
confidence: 99%